Successful implantation of a permanent pacemaker through a persistent left superior vena cava by using a right subclavian approach - Jović Zoran; Mijailović Zdravko; Obradović Slobodan; Tavčiovski Dragan; Matunović Radomir; Rusović Siniša; Đurić Predrag (Vojnosanitetski Pregled)
Introduction. Persistent left superior vena cava, a rare congenital abnormality, can complicate placement of pacemaker leads through the subclavian vein. A left-sided approach is usually preferable in such cases. Case report. We reported a case in which we began a single-chamber pacemaker implantation procedure via a right subclavian approach (because of scarring beneath the left clavicle) and then discovered intraoperatively that the patient had a persistent left superior vena cava. After a few attempts, we succeeded in placing the head of the electrode in the septum, near the top of the right ventricle, and the rest of the procedure was completed without complication. Conclusion. To our knowledge, this is the first reported case of pacemaker implantation, with passive electrode, through a persistent left superior vena cava via the right subclavian vein. This case demonstrates that such an approach, when necessary, can be used successfully.